EMS Induced Cytomictic Variability in Safflower (Carthamus tinctorius L.) - Srivastava, P.; Kumar, G. (Цитология и генетика, 2011)
Seeds of safflower (Carthamus tinctorius L.) were subjected to three treatment durations (3h, 5h and 7h) of 0.5 % Ethyl Methane Sulphonate (EMS). Microsporogenesis was carried out in the control as well as in the treated materials. EMS treated plants showed interesting feature of partial inter-meiocyte chromatin migration through channel formation, beak formation or direct cell fusion. Another interesting feature noticed during the study was the fusion among tetrads due to wall dissolution. The phenomenon of cytomixis was recorded at nearly all the stages of microsporogenesis connecting from a few to several meiocytes. Other abnormalities such as laggards, precocious movement, bridge and non disjunction of chromosomes were also recorded but in very low frequencies. The phenomenon of cytomixis increased along with the increase in treatment duration of EMS. Cells with these types of cytomictic disturbances may probably result in uneven formation of gametes or zygote, heterogenous sized pollen grains or even loss of fertility in future. Семена сафлора (Carthamus tinctorius L.) обрабатывали 0.5%-ным этилметансульфонатом (ЭМС) в одном из трех режимов – 3, 5 и 7 ч. Микроспорогенез изучали как в контроле, так и в обработанном материале. Растения, обработанные ЭМС, проявляли интересную особенность частичной интермейоцитной миграции хроматина при формировании каналов, образовании клювообразного выступа или прямом слиянии клеток. Другим обнаруженным в исследовании явлением было слияние тетрад из-за растворения стенки. Феномен цитомиксиса отмечался почти на всех стадиях микроспорогенеза и затрагивал от нескольких до многих мейоцитов. Другие аномалии, такие как отставания, преждевременные движения, мосты и неразделения хромосом, отмечались с незначительной частотой. Феномен цитомиксиса возрастал с увеличением длительности обработки ЭМС. Клетки с этими типами цитомиктических нарушений могут, вероятно, приводить к нерегулярному формированию гамет или зигот, гетерогенных по размеру пыльцевых зерен, или даже к потере фертильности в будущем. Насіння сафлору (Carthamus tinctorius L.) обробляли 0.5%-ним етилметансульфонатом (ЕМС) в одному з трьох режимів – 3, 5 і 7 год. Мікроспорогенез вивчали як у контролі, так і в обробленому матеріалі. Рослини, оброблені ЕМС, виявляли цікаву особливість часткової інтермейоцитної міграції хроматину при формуванні каналів, утворенні дзюбоподібного чи прямому злитті клітин. Іншим виявленим в дослідженні явищем було злиття тетрад через розчинення стінки. Феномен цито- міксису відзначався майже на всіх стадіях мікро-спорогенезу і зачіпав від кількох до багатьох мейоцитів. Інші аномалії, такі як відставання, передчасні рухи, мости і нерозділення хромосом, зустрічались з незнач- ною частотою. Феномен цитоміксису зростав із збільшенням тривалості обробки ЕМС. Клітини з цими типами цитоміктичних порушень можуть, ймовірно, приводити до нерегулярного формування гамет або зигот, гетерогенних за розміром пилкових зерен, або навіть до втрати фертильності в майбутньому.